Identity: Socio-Political, Sociological, Humanistic and Poststructuralist Perspectives - Salamanca González, Fredy Orlando (Universidad Pedagógica y Tecnológica de Colombia, 2015)
Identity hasmultiple definitions and is related to many fields and theoreticians. It iscommonly believed that each person possesses one single and personal identity, but several perspectives have proposedmultiple dimensions for it. This article presents some dimensions about what the termidentity involves fromthe socio-political, sociological, humanistic, social and poststructuralist perspectives. Despite identity is displayed by people, is perceivable, transmittable, influenced by many factors, defining identity can get anywhere depending on the path to follow. The only certainty is that motivation, desires, preferences, ideology, words, tones, interjections, and clothing are issues related to identity.